2014
DOI: 10.4028/www.scientific.net/amm.687-691.359
|View full text |Cite
|
Sign up to set email alerts
|

Research on Modeling and Optimization Control of Heavy Truck Cab Active Suspension System

Abstract: In order to meet the ride comfort of the heavy truck cab, the 1/2 heavy truck cab active suspension model established. Based on this model the LQG optimization control was selected for the active control of a 1/2 heavy truck cab suspension system. The road disturbance is integral white noise stochastic signal. By the example simulation in Matlab/Simulink, the results show that the cab active suspension with LQG control strategy can decrease the vertical accelerations, the roll angle and roll angle acceleration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Guang and Shuo 13 used a half truck model with active cab suspension system considering the linear quadratic Gaussian (LQG), and also an optimal control strategy was used for the active cab suspension for optimizing the control study. The results showed that the root mean square (RMS) of the cab vertical acceleration and pitch acceleration could be improved using the LQG strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Guang and Shuo 13 used a half truck model with active cab suspension system considering the linear quadratic Gaussian (LQG), and also an optimal control strategy was used for the active cab suspension for optimizing the control study. The results showed that the root mean square (RMS) of the cab vertical acceleration and pitch acceleration could be improved using the LQG strategy.…”
Section: Introductionmentioning
confidence: 99%